Evaluating Role Of Ultrasound And Mrcp In Diagnosing Causative Factors Of Obstructive Jaundice (Journal of Pharmaceutical Negative Results, 2022)
Though Ultrasonography and CT are noninvasive, they have their own disadvantages as well. Ultrasound is not effective in accurately diagnosing the site of obstruction in many cases. Computed Tomography has an increased risk of radiation as well as decreased sensitivity or detecting stones. Intravenous cholangiography has its own limitations as in one third to one fourth of the cases there is no complete opacification of the biliary tract and increased number of cases show contrast reaction as well. “ERCP and PTC are not simple procedures and require technical experience and contrast media. To add to the difficulties also several complications from the procedure may arise.”“Other imaging techniques used in the diagnosis of biliary tree and pancreatic duct are Ultrasonography, Computed Tomography, IV cholangiography and Endoscopic Retrograde Cholangiopancreatography (ERCP) and Percutaneous Transhepatic Cholangiography (PTC). For patients with suspected ductal pathology there are advantages and disadvantages which are unique to the specific technology.”